An atypical right ventricle-dependent coronary circulation in a child with pulmonary artery stenosis. (June 2018) - Tahhan, Nabil; Houyel, Lucile; Petit, Jerome; Horer, Jurgen; Hascoet, Sebastien
Abstract: Right ventricle-dependent coronary circulation (RVDCC) is associated with pulmonary valve atresia and intact ventricular septum (PA-IVS). Currently, the suggested mechanism of coronary artery fistulas in PA-IVS is a primary anomaly of RV development, leading to progressive pulmonary atresia and development of abnormal fistulous communications between coronary arteries and the right ventricular cavity. We report the first case of RVDCC in a child with main pulmonary artery stenosis and normal RV development. Highlights: This case report shows a right and left coronary arteries-right ventricle fistulas with a right ventricle-dependent coronary circulation in a child with main pulmonary artery stenosis and normal RV development. For the right ventricle-dependent coronary circulation, it has been recently suggested that the primary disease may be a structural anomaly of the right ventricular. In this case, the RV exhibited normal morphology, this finding appears inconsistent with recent suggestions.